Análisis para el desarrollo de un sistema de control de venta de Mariscos Guillermo perteneciente a la ciudad de Babahoyo. - Tenorio Bazán, Alex Joel (2023)
Businesses must always be prepared and attentive to changes in the environment, as these can negatively affect them if they do not act and adapt. Nowadays, we live in an era of consumerism, where there are always people with needs to acquire products, either because they like them or because they need them. Therefore, it is essential that both large and small companies are able to meet these needs, and if necessary, make changes to move forward in the market. The integration of the knowledge acquired in the research will make it possible to identify areas for improvement in the seafood sales process, as well as opportunities for innovation and the implementation of a control system that will allow for more efficient and effective management of the business. In the synthesis of the research, the results obtained will be presented and their implications will be discussed. In addition, recommendations will be proposed for the implementation of the seafood sales control system, with the objective of improving management and increasing the profitability of the business. To carry out this analysis, various methods will be used to collect and analyze information, such as interviews with the owner and surveys of workers and customers, direct observation of the sales process, analysis of documents and sales records, among others. Through these methods, it will be possible to obtain detailed information on the operation of the business and the seafood sales processes. The objective of the research is to identify the problems and opportunities for improvement in the process of selling seafood in the Guillermo business, in order to implement a control system that allows a more efficient and effective management of the business, thus improving its profitability and positioning in the market.